The prevalence of domestic distribution for bugs Cimex lectularius (L. ) in Dhamar - alsanabani, abdulwahab (Yemeni Journal of Agriculture & Veterinary Sciences, 2021)
Household Bugs (bed bugs) snooped object externally on human organisms warm-blooded birds, rodents and domesticated animals. The study was conducted for the purpose of identifying the household bugs and the extent of the percentage spread and wherever they are located in different areas in the city of Dhamar, during the period from May to August 2013. The study groups were divided into the first two groups consisted of hotels and guest houses for the bed of workers and others, as well as shops used to spend the night in Dhamar where I took the averages for each of these sites, where the total number of adult women in this group (315) seriously by (49.8%). The second group was made to the restrooms and only represented the district (residential market Rabua, home and street Rada and the Western Ring Road) by a very 317 seriously by (50.2%)results shown in the first study, the presence of bugs in abundance Breaks 180 seriously (28.5%), followed by shops, 90 (14%) and 45 hotels (7%) The second group showed an abundance object district Rada Street 152 highly (24%), followed by Rabua market district 46 seriously (7.3%), and 44 residential neighborhood very (7%), and 35 great-west (5.5%) followed by 25 home neighborhood very (4%) and finally neighborhood Taiz St. 15 seriously 2.4%),. During the results there is only one type only in this thoughtful places